Vaccination Week in the Americas: An Opportunity to Integrate Other Health Services With Immunization - Ropero-Álvarez, Alba Maria (Oxford University Press, 2012)
Vaccination Week in the Americas (VWA) is an initiative of the countries and territories of the Americas that works to advance equity and access to vaccination. The initiative focuses on reaching populations with limited access to regular health services and promotes solidarity among countries. As the Expanded Program on Immunization is one of the world’s best-established health programs, integrating other interventions with immunization services has been highly promoted. Using data available from the Pan American Health Organization, we explored the extent of integration of other interventions with immunization in Latin American and Caribbean (LAC) countries as part of VWA. At least 14 countries or territories have integrated other interventions with immunization during VWA. The most common integrated intervention is vitamin A supplementation, followed by deworming. However, a variety of other interventions have been integrated, such as educational activities, supplementation with vitamins and minerals, and provision of health services. Data on coverage of integrated interventions are limited. Integration of other interventions with immunization in LAC countries is widespread, and its impact and lessons learned merit further examination.